2022
DOI: 10.1037/men0000372
|View full text |Cite
|
Sign up to set email alerts
|

“I didn't know who to talk to”: Black college men’s sources and descriptions of social support.

Abstract: Young Black men face unique interpersonal challenges throughout their time on college campuses, as they are forced to navigate anticipated developmental stressors (e.g., academic adjustment), coupled with racespecific microaggressions and structural forms of harm. Still, members of this group remain underrepresented in higher education, and their lived experiences have been neglected within existing men's studies research. Therefore, carefully examining Black college men's forms of social support is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…AAMCS have access to mental health services on college campuses, however, that does not always mean greater counseling use. Goodwill et al (2022) found that many Black male freshmen college students did not know who to turn to when experiencing emotional equilibrium, adjustment to college issues, and challenges to masculinity. This is also corroborated by further research in which college-aged men tend to have lower AMHI in comparison to women on campuses (DeBate et al, 2018; Stansbury et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…AAMCS have access to mental health services on college campuses, however, that does not always mean greater counseling use. Goodwill et al (2022) found that many Black male freshmen college students did not know who to turn to when experiencing emotional equilibrium, adjustment to college issues, and challenges to masculinity. This is also corroborated by further research in which college-aged men tend to have lower AMHI in comparison to women on campuses (DeBate et al, 2018; Stansbury et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Social support systems are protective across all populations, but they may be of particular importance to Black men, because they may influence aspects of racial identity, such as private and public regard (Garrett-Walker & Longmire-Avital, 2018; Goodwill et al, 2022). A recent longitudinal study found that Black college students ( n = 171) who had higher levels of private regard at baseline had lower levels of psychological distress 3 years later (Willis & Neblett, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much has been written about the experiences of Black students at predominantly White institutions (Billingsley & Hurd, 2019; Goodwill et al, 2022; Griffith et al, 2019). Black students in predominantly White institutions (PWIs) are more likely to encounter race-related stressors than those attending historically Black institutions (Greer & Chwalisz, 2007).…”
Section: Related Literaturementioning
confidence: 99%